Comparison of Frequency of Postpartum Haemorrhage in Augmented Versus Spontaneous Labour: Postpartum Haemorrhage in Augmented Versus Spontaneous Labour - Tariq, Maryam; Rafeeq, Sitara; Jadoon, Samina; Ara, Chaman; Hamid, Beenish Samreen; Rauf, Isma (Pakistan Journal of Health Sciences, 2025)
Postpartum haemorrhage (PPH) remains a major cause of maternal morbidity and mortality. Labour augmentation is commonly practiced but may increase the risk of excessive bleeding. Objectives: To determine the frequency of PPH and compare its occurrence in spontaneous versus augmented labour. Methods: A descriptive cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, Mardan Medical Complex, from August 2023 to January 2024. A total of 151 women aged 18–40 years with singleton pregnancies at ≥36 weeks were enrolled using non-probability consecutive sampling. Data on age, parity, gestational age, hypertension, socioeconomic and residential status, labour type, and PPH were collected through a structured proforma. PPH was defined as blood loss >500 ml within 24 hours of vaginal delivery. Data were analyzed using SPSS version 25.0, and associations were tested using Chi-square and Fisher’s exact tests. Results: The frequency of PPH was 13.2%. PPH occurred more frequently in spontaneous labour (15.7%) compared to augmented labour (10.3%), though this was not statistically significant (p=0.333). A significant association was found between hypertension and PPH (p=0.017), with hypertensive women showing a higher risk. Conclusions: It was concluded that Hypertension was significantly associated with postpartum haemorrhage, underscoring the importance of careful monitoring. Labour augmentation did not significantly increase PPH risk. Ongoing evaluation of maternal risk factors is crucial for improving outcomes.